Fungsi Bahasa Register Taruna Akademi Militer - Ilyas, Patmawati; Farikah; Mulyani, Mimi (Kajian Bahasa dan Sastra (KABASTRA), 2021)
Language-speaking communities have a variety of languages ​​depending on the context or situation and the social factors surrounding them. Social factors which are the different factors in using the language brings out a language variation that distinguishes one language from other languages ​​which are called register. In its use, the register has various functions depending on what, with whom, and how the register is used to interact or communicate. Military Academy cadet is one of the groups who have registered. In their daily life, Military Academy cadets are educated by strict military rules. One of these rules relates to how to communicate between cadets of the same age, junior cadets and senior cadets, as well as between cadets and coaches, caregivers, or the workers (civil servant or army) in Military Academy. This article will describe the register and its functions in cadet conversations in Military Academy.